Bea Scoring System: Selecting the Right Person for Scholarship - Sharif, Shamshuritawati; Ismail, Suzilah; Ahmad, Yuhaniz; Khalid, Ruzelan; Omar, Mohd. Faizal; Zain, Zakiyah (International Journal of Economics and Financial Issues, 2015)
Disability may involve visual disability, physical disability, learning disorder, speech disorder, mental disorder and others various disabilities. This situation can reduce the quality of life, and causes clear drawback to that person. Due to this, in many countries, there are scholarships for students with disability, and students with disability parents. Universiti Utara Malaysia also provides a scholarship known as Bestari Education Award (BEA) scheme to assist poor students with disability. The process of selecting the right student for the scholarship is through a manual approach by analyzing the individual application forms and usually very time consuming. In this study, a scoring system is developed to simplify the selection process. The score is based on monthly household income, number of dependents and taking into consideration any disabilities, critical illnesses, orang asli and orphan. This scoring system can replace the long manual process of analyzing the forms and assist administrative to strategize the management of this special scheme. Keyword: Financial Assistance; Manual Selection; Scoring System JEL Classifications: C60; I24